The relationship between certain factors and adolescents' decision to engage in sex - Dalumpines, Renel H. (2004.)
The study aims to determine whether there is a relationship between certain factors and adolescents decision to engage in sex. It seeks to accomplish the following objectives: (1)To identify the risks perceived by adolescents when or if they engage in a sexual activity. (2)To determine if there is a relationship between adolescents' relationship with their parents and their decision to engage in a sexual activity. (3)To ascertain if there is a relationship between adolescents' perception of the sexual activity status of other adolescents they closely interact with and their decision to engage in a sexual activity. (4)To find out if there is a relationship between adolescents' perceived risks and their decision to engage in a sexual activity. (5)To know if there is a relationship between adolescents' level of religiosity and their decision to engage in a sexual activity., The respondents of the study are students of the Division of Social Sciences, College of Arts and Sciences of the University of the Philippines in the Visayas. Sixty respondents were randomly chosen from a population of 428. The survey conducted enabled the researcher to conclude that of the four factors that were considered, only two factors, namely: the perception of the sexual activity status of peers and the level of religiosity, have a relationship with the decision of adolescents to engage in sex. The other two, which were the level of parental relationship that was measured by the agreement of the adolescents on their parents' ideas regarding parental discipline and the perceived risks when engaging in sex, are not related to the decision of adolescents to engage sex in this study. The researcher recommends that further research be designed to find out how long the respondents have been engaging in sex and how far have they gone in terms of the sexual activities they have engage in.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Adolescents